The acute effects of resistance exercise with blood flow and respiratory restriction on blood lactate and growth hormone in collegiate wrestlers - Rahmani, A.; Mirzaei, B. (International Journal of Wrestling Science, 2018)
Resistance activity with new methods of exercise such as blood flow and respiration restriction has been performed at a lower intensity in pursuing various physiological responses. The main purpose of this research was to study the effect of blood flow and respiratory restriction on blood lactate concentration and growth hormone in the acute response to resistance exercise in collegiate wrestlers. A counter- balanced design was used in which 8 collegiate wrestlers (mean age 26.87±4.7 years and body mass index 25.26±2.49 kg/m2) were randomly assigned in three conditions including: control (80%1RM) and resistance exercise with blood flow and respiratory restriction (30%1RM). Four sets of squats were used as the resistance exercise. Blood samples were collected before and immediately after exercise. The data were analyzed by repeated measure ANOVA using SPSS software (version 19) with a significance level of p <0.05. All three types of exercise caused a significant increase in lactate and growth hormone immediately after the exercise, but no significant difference was observed between the groups. The results of this study indicated that resistance exercise with restriction of blood flow and respiration can lead to increased metabolic and hormonal responses. This research also confirms the effectiveness of this type of exercise and satisfies the goals expected from high intensity exercises.